Cytological, hormonal, and ovarian hemodynamic alteration during the normal oestrus and split heat cycles in bitches - Abdallah, Asmaa A.; Abdelnaby, Elshymaa A.; Amin, Said; El-Sherbiny, Hossam R.; Emam, Ibrahim A.; Ibrahim, Fatma M. (Journal of Advanced Veterinary Research, 2024)
Hormonal levels, particularly progesterone (P4), could be used to predict the day of luteinizing hormone (LH) surge, which is important not only for optimum ovulation but also for the detection of some abnormalities such as split heat. This study aimed to determine cytological, hormonal, and ovarian vascularity changes in normal cyclic and split heat bitches during proestrus and estrous phases. Pluriparous females (n=40) were categorized into two groups as follows: Group A (n=35; with a normal sequence of oestrus cycle) and Group B (n=5; split heat females with a short duration of proestrus). Doppler and hormonal assessments were performed daily from day 0 until day 15. Compared to Group B, both ovarian arteries (OA) Doppler indices decreased in Group A, with the most significant decline occurring between days 7 and 12. While peak velocity (PSV; cm/sec) was elevated in Group A compared to its value in Group B. In Group A, estradiol (E2) levels were higher (P 0.05) than in Group B, with the most significant increase observed between days 7-12. Group A showed an increase in nitric oxide (NO) from days 8 to 12 with no change in split heat bitches (P<0.05). P4 levels were slightly elevated (P<0.05) until they reached 3.5±0.09 and 8.25±0.22 ng/ml on days 10 and 15, respectively. Nevertheless, bitches showed split heat in Group B, P4 level was low. In Group A, IGF-1 levels were elevated in the proestrus phase until day 9 (155.32±5.26) and in the estrous phase until day 15 (175.56±3.66) compared to other groups. In Group B, the dominance of small intermediate cells and RBCs on all days remained unchanged on all days, in contrast to Group A, where cornified cells began to dominate on day 15. In conclusion, these data suggested that the evaluation of ovarian hemodynamics, in addition to hormonal and cytological assessments, could be critical parameters not only for the optimum ovulation prediction by progesterone assay related to LH but also for the detection of any abnormalities such as split heat or irregular estrous interval.